2020
DOI: 10.1186/s12915-020-00812-5
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionarily conserved ESRE stress response network is activated by ROS and mitochondrial damage

Abstract: Background Mitochondrial dysfunction causes or contributes to a wide variety of pathologies, including neurodegenerative diseases, cancer, metabolic diseases, and aging. Cells actively surveil a number of mitochondrial readouts to ensure that cellular homeostasis is maintained. Results In this article, we characterize the role of the ethanol and stress response element (ESRE) pathway in mitochondrial surveillance and show that it is robustly activated when the concentration of reactive oxygen species (ROS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 83 publications
3
26
0
Order By: Relevance
“…Previous work from our lab has established that the ESRE network plays an important role in the resistance of C. elegans to pyoverdine, the main virulence determinant in Liquid Killing, and recent evidence has shown that ESRE activation depends on increased reactive oxygen species (ROS) [22,37,38]. To evaluate ESRE activation, worms carrying an hsp-16.1p::GFP reporter (which contains two ESRE motifs and was previously used as an indicator of ESRE activation [38][39][40]), were exposed to 50 or 100 μM LK35, LK38, LK56, juglone (positive control [37,41]), or DMSO. Only treatment with In a similar approach, we tested for UPR ER stress using a GFP transcriptional reporter for hsp-4, the C. elegans homolog of BiP (S1C None of compounds activated these pathways at either concentration.…”
Section: The Activity Of Lk Molecules Is Not Mediated By Conventionalmentioning
confidence: 99%
“…Previous work from our lab has established that the ESRE network plays an important role in the resistance of C. elegans to pyoverdine, the main virulence determinant in Liquid Killing, and recent evidence has shown that ESRE activation depends on increased reactive oxygen species (ROS) [22,37,38]. To evaluate ESRE activation, worms carrying an hsp-16.1p::GFP reporter (which contains two ESRE motifs and was previously used as an indicator of ESRE activation [38][39][40]), were exposed to 50 or 100 μM LK35, LK38, LK56, juglone (positive control [37,41]), or DMSO. Only treatment with In a similar approach, we tested for UPR ER stress using a GFP transcriptional reporter for hsp-4, the C. elegans homolog of BiP (S1C None of compounds activated these pathways at either concentration.…”
Section: The Activity Of Lk Molecules Is Not Mediated By Conventionalmentioning
confidence: 99%
“…Pyoverdine translocated from the intestinal lumen into host tissue, disrupting iron and mitochondrial homeostasis [ 24 , 25 ]. Pyoverdine also inhibited redox metabolism and ATP synthesis, and activated mitochondrial quality control pathways [ 24 , 26 , 27 ]. Some combination of these functions makes pyoverdine critical for P. aeruginosa virulence in invertebrate hosts (such as C. elegans and Galleria mellonella ) [ 23 , 28 ] and in murine infection [ 5 , 10 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work from our lab has established that the ESRE network plays an important role in the resistance of C. elegans to pyoverdine, the main virulence determinant in liquid killing, and recent evidence has shown that ESRE activation depends on increased reactive oxygen species (ROS) ( 23 , 38 , 39 ). To evaluate ESRE activation, worms carrying an hsp-16.1p ::GFP reporter (which contains two ESRE motifs and was previously used as an indicator of ESRE activation [ 39 – 41 ]), were exposed to 50 or 100 μM LK35, LK38, LK56, juglone (positive control [ 38 , 42 ]), or DMSO. Only treatment with LK56 at 100 μM resulted in weak activation of ESRE (see Fig.…”
Section: Resultsmentioning
confidence: 99%